FREEDOM OF THOUGHT IN SAMAN NOVEL BY AYU UTAMI (1998): A GENETIC STRUCTURALIST APPROACH - Libriani, Ika; Candraningrum, Dewi; Setyabudi, Titis (Universitas Muhammadiyah Surakarta, 2015)
AbstractThis study examined the world view of freedom of thought of the majorand minor characters in Saman novel by involving genetic structuralistapproach. This research was descriptive qualitative research. The primarydata source was Saman, a novel written by Ayu Utami and translated byPamela Allen in 2005. Meanwhile the secondary data source was the socialhistoricalbackground of the Indonesian society in the twentieth century. Bothdata were collected through library research and analyzed by descriptiveanalysis. Based on the genetic structuralist approach, there was a closerelationship between the novel and the realities of Indonesian life. The novelwas as an object in which the author presented her world view.Keywords: Freedom of Thought, Saman, Genetic Structuralist Approach.Â